Evidence for two functionally distinct subpopulations of neurons within the rat striatum - Nisenbaum, ES (J Neurosci, 1988)
Type I and Type II extracellular action potential waveforms were recorded from the rat striatum and studied with respect to their dependence on recording conditions, response to paired impulse stimulation of the corticostriatal pathway, and iontophoretic application of dopamine (DA). Results showed that the distinguishing characteristics of Type I and Type II waveforms are relatively independent of the degree of filtering, distance of the electrode tip from the target neuron, type of recording electrode, and firing rate of the neuron. Very low impedance electrodes, however, were found to mask the difference in spike shape. Electrical stimulation of cortical afferents results in excitation of both action potential waveforms, though the Type II class exhibits a significantly shorter latency than the Type I class. Paired impulse analyses revealed that both waveforms exhibit variation in the probability of discharge (facilitation or inhibition) to the second impulse of each impulse pair that are a function of the interimpulse interval. Most importantly, however, the probabilities of discharge of Type I and Type II neurons to the second impulse are inversely related, i.e., when one cell type exhibits facilitation, the other displays inhibition. These data demonstrate that Type I and Type II waveforms represent the activity of functionally different subpopulations of striatal neurons. Moreover, Type II neurons are found much more often than Type I cells, suggesting that the 2 cell classes may be represented with different frequencies within striatum. Finally, Type II neurons display at least a 5 times greater sensitivity to iontophoretically applied DA than Type I cells, suggesting that the 2 cell populations also are affected differentially by dopaminergic input from the substantia nigra.